Cross-well seismic waveform tomography for monitoring CO2 injection: A case study from the Ketzin Site, Germany - Zhang, F.; Juhlin, Christopher; Cosma, C.; Tryggvason, A.; Pratt, R. (2012)
Geological storage of CO2 is one means of mitigating the effects of continued burning of fossil fuels for power generation. An important component in the storage concept is the monitoring of the CO2 distribution at depth. Seismic methods can play a significant role in this monitoring, in particular cross-well methods are of interest due to their high resolution. For these purposes, a series of cross-well seismic surveys were acquired within the framework of the CO2SINK project at Ketzin, Germany, at various stages of an injection test. We study here the potential of applying cross-well seismic waveform tomography to monitor the CO2 injection process. First, we test the method on synthetic data having a similar geometry to that of the real data. After successful application on the synthetic data, we test the method on the real data acquired at the Ketzin Site. Traveltime tomography images of the real data show no observable differences between the surveys. However, seismic waveform tomography difference images show significant differences. A number of these differences are artefacts that can probably be attributed to inconsistent receiver coupling between the different surveys. However, near the injection horizon, below the caprock, a velocity decrease is present that is consistent with that expected from the injection process.